Income dynamics in Tamil Nadu, India from 1971 to 2003: changing roles of land and human capital - Kajisa, Kei; Palanichamy, N. Venkatesa (Wiley, 2006)
This article examines the changing role of physical and human capital in income dynamics in Tamil Nadu, India, using detailed daily records of farming households from 1971 to 2003. We find that income growth until the early 1990s is attributed to the rice Green Revolution and the associated development of nonrice farm sector. Further growth after the 1990s became possible due to the rapid nonfarm sector development that has been stimulated by the liberalization of Indian economy since 1991. In accordance with this change in income structure, the importance of physical and human capital has changed. Human capital was important in the early 1970s to take advantage of the rice Green Revolution technology. Once the new technology became standard among farmers, human capital became an insignificant factor. The importance of human capital has revived in a different manner in recent years firstly because it has increased farmers' access to nonfarm job opportunities, and secondly because farm management has become more knowledge intensive in the face of increasing scarcity of labor and water. The contribution of physical capital increased during the Green Revolution period, while it started declining after that. The changing mechanism is characterized as the shifting importance from physical to human capital in accordance with the changing engines of income growth from the Green Revolution to the development of nonfarm sector.